Traditional market governance nagari koto baru X koto tanah datar district West sumatra (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The traditional market is a supporting sector in the community's economy. However, the existence of traditional markets also has several aspects of weakness that really need to be rearranged again. Likewise with the existence of a traditional market in the new Koto village, X Koto District, Tanah Datar Regency, West Sumatra Province, which has experienced many problems. This study used qualitative research methods. Qualitative research is research to find out a phenomenon as it is from a research topic. Thus, for this reason, the topic of the unit of analysis in this study is the Management of the Koto Baru Traditional Market, X Koto District. Based on research results, one of the phenomena that often occurs in Pasar Koto Baru is the frequent traffic jams that occur every Monday. This happened because Pasar Koto Baru is the largest central vegetable market in West Sumatra, but the location of Pasar Koto Baru is narrow. So that with these market conditions, the Koto Baru market has piles and spills of vegetables all the way to the Padang Bukittingg main road every Monday. In addition to the problem of spatial management of the Koto Baru market, other problems can also be seen in the Koto Baru market, such as the problem of piles of garbage in the Koto Baru market. This happens because there is no landfill. Garbage must be brought to the TPA in Batusangkar. However, the management of the various problems that occurred in the Koto Baru market was good because the Tesebur market was directly managed by the Koto Baru village government, X Koto Baru District, Tanah Datar Regency. Management of retribution already . Thus it will become the government's capital in an effort to improve the reorganization of the Koto Baru market more optimally. The existence of the Koto Baru market greatly boosted the economy of the people of Koto Baru country